Effects of Spray Drying and Spray Chilling on Ibuprofen Dissolution: Dissolution of spray dried and spray chilled ibuprofen - Amal A. Elkordy,; Ebtessam A. Essa, (Iranian Journal of Pharmaceutical Sciences, 2010)
The formulation of hydrophobic drugs for oral drug delivery is challenging due to poor solubility, poor dissolution and poor wetting of these drugs. Consequently, the aim of this study was to improve the dissolution of a model poorly water soluble drug, ibuprofen. Microparticles containing ibuprofen were produced by spray drying and spray chilling technology in the absence/presence of a hydrophilic surfactant. Poloxamer 127, tri-block copolymer, was chosen as the hydrophilic surfactant to improve drug particle wettability and hence the dissolution rate. The prepared formulations were evaluated for in vitro dissolution and intrinsic solubility. In addition, the produced drug particles were characterised by scanning electron microscopy (SEM), differential scanning calorimeter (DSC) and Fourier transform infrared spectroscopy (FT-IR). SEM revealed changes in the surface morphology of processed ibuprofen, suggesting the effective formation of the drug particles. DSC data showed shifting of the melting peak of the drug towards lower melting temperature in the prepared particles, indicating the possibility of drug /polymer interaction. The results of the dissolution studies of spray dried ibuprofen and spray dried ibuprofen/Poloxamer 127 particles significantly (p<0.05) increased the percentage of drug release compared to the control (ibuprofen raw material). For spray chilling, the prepared particles did not improve the dissolution of the drug. The dissolution was even less than that of the control. DSC and FT-IR results demonstrated that spray drying reduced drug crystallinity, but for spray chilled particles there was evidence of polymorphic changes in the drug with and without the surfactant. Consequently, it is believed that spray drying of ibuprofen is a useful tool to improve wettability, solubility and hence the dissolution behavior of poorly water soluble drugs, in contrast to spray chilling technique.